Stroke nurse navigator utilization reduces unplanned 30-day readmission in stroke patients treated with thrombolysis - Jun-O'Connell, Adalia H.; Grigoriciuc, Eliza; Gulati, Akanksha; Silver, Brian; Kobayashi, Kimiyoshi J.; Moonis, Majaz; Henninger, Nils (Frontiers in Neurology, 2023)
Background: Unplanned 30-day hospital readmissions following a stroke is a serious quality and safety issue in the United States. The transition period between the hospital discharge and ambulatory follow-up is viewed as a vulnerable period in which medication errors and loss of follow-up plans can potentially occur. We sought to determine whether unplanned 30-day readmission in stroke patients treated with thrombolysis can be reduced with utilization of a stroke nurse navigator team during the transition period. Methods: We included 447 consecutive stroke patients treated with thrombolysis, included in an institutional stroke registry between January 2018 and December 2021. Control group consisted of 287 patients before the stroke nurse navigator team implementation between Jan 2018 and August 2020. The intervention group consisted of 160 patients after the implementation during September 2020 and December 2021. The stroke nurse navigator interventions included medication reviews, hospitalization course review, stroke education, and review of outpatient follow-ups within 3 days following the hospital discharge. Results: Overall, baseline patient characteristics (age, gender, index admission NIHSS, and pre-admission mRS), stroke risk factors, medication usage, and length of hospital stay were similar in control versus intervention groups (P>0.05). Differences included higher mechanical thrombectomy utilization (35.6% vs. 24.7%, P=0.016), lower pre-admission oral anticoagulant use (1.3% vs. 5.6 %, P=0.025), and less frequent history of stroke/TIA (14.4 % vs. 27.5%, P=0.001) in the implementation group. On unadjusted Kaplan-Meier analysis, 30-day unplanned readmission rates were lower during the implementation period (Log-rank P=0.029). After adjustment for pertinent confounders including age, gender, preadmission mRS, oral anticoagulant use, and COVID-19 diagnosis, the nurse navigator implementation remained independently associated with lower hazards of unplanned 30-day readmission (adjusted HR 0.48, 95% CI 0.23-0.99, P=0.046). Conclusion: Utilization of a stroke nurse navigator team reduced unplanned 30-day readmissions in stroke patients treated with thrombolysis. Further studies are warranted to determine whether results extent to stroke patients not treated with thrombolysis and to better understand the relationship between the resource utilization during transition period from discharge with quality outcomes in stroke.